Pengaruh Religiusitas Dan Budaya Terhadap Prilaku Konsumen Muslim Dalam Membeli Makanan Kafe - Rezkina Hayati; Iiz Izmuddin; Anne Putri (EKONOMIKA SYARIAH : Journal of Economic Studies, 2019)
This research attempts to analyze the effect of religiosity and culture on purchasing decisions in buying cafe food in Bukittinggi partially or simultaneously. The design of this study is quantitative correlational. The population is Muslim teenagers in the city of Bukittinggi. The sample of this study was Muslim teenagers in the Bukit Tinggi town who bought cafe food. Furthermore, the determination of the sample to be used as the respondent was done by purposive sampling, by taking and selecting Muslim adolescents in Bukittinggi as respondents.Based on the results of the study it can be concluded that: partially Religiosity and Culture have a positive effect on purchasing decisions in buying cafe food, while Religiosity and Culture simultaneously influence purchasing decisions in buying cafe food where the contribution of the determination coefficient (R Square) is 38.8% and the remaining 61.2% is influenced by other variables which are not included in this similarity regression or variables not examined.